Treatment with Short Wave Diathermy on Chronic Low Back Pain (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7669 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):40-44